Characterizing grower performance, body conformation and morphology in crosses of RIR and Indian native chicken genotypes - DAS, ANANTA KUMAR; MISHRA, ANIL KUMAR; KUMAR, SANJEEV; RAHIM, ABDUL; KOKATE, LAXMIKANT SAMBHAJI (The Indian Journal of Animal Sciences, 2017)
The day-old chicks of RIRf × AseelM and RIRf × KadaknathM crosses were investigated to characterize their grower performance, body conformation and morphological characteristics. The progeny of RIRf × AseelM cross exhibited heavier body weights and greater estimates of body conformation traits throughout the age than in the RIRf × KadaknathM cross with significant sex-differences and lower to higher range of phenotypic correlations at positive direction among the traits. Both the crosses also exhibited different colours of shank, skin, beak, comb, eye, earlobe, wattle, body plumage along with its pattern, comb type and pattern within feather with sex differences for some characteristics when observed their progenies at 12th week of age. These cross specific findings might serve as the cross identification earmarks.